2019
DOI: 10.1016/j.ridd.2019.103498
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual profile in school-aged children with borderline intellectual functioning

Abstract: Background: Little is currently known about borderline intellectual functioning (BIF), a condition characterized by an intelligence quotient between one and two standard deviations below the average, that affects about 14% of the population. Aims: The present study aimed to analyze the intellectual profile of school-aged children with BIF. Method and Procedure: The WISC-IV was administered to 204 children with BIF attending Italian primary and lower secondary school, and their profile was compared with that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…BIF is a condition characterized by a mental functioning at the border between normal intellectual functioning and intellectual disability, which means an IQ within 1 and 2 standard deviations below the mean of the normal curve of the distribution of intelligence with an impact on adaptive abilities (Salvador-Carulla et al, 2013;Wieland and Zitman, 2016). In primary school age, children with BIF present major difficulties in school achievements due to learning difficulties in more than one domain, difficulties in executive functions, such as attention, concentration, planning, and inhibition of impulsive responses, in memory, and motor skill limitations (Alloway, 2010;Vuijk et al, 2010;Salvador-Carulla et al, 2013;Pulina et al, 2019). Furthermore, limitations in social skills, emotional competencies and behavioral problems affect social participation of these children (Kavale and Forness, 1996;Baglio et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…BIF is a condition characterized by a mental functioning at the border between normal intellectual functioning and intellectual disability, which means an IQ within 1 and 2 standard deviations below the mean of the normal curve of the distribution of intelligence with an impact on adaptive abilities (Salvador-Carulla et al, 2013;Wieland and Zitman, 2016). In primary school age, children with BIF present major difficulties in school achievements due to learning difficulties in more than one domain, difficulties in executive functions, such as attention, concentration, planning, and inhibition of impulsive responses, in memory, and motor skill limitations (Alloway, 2010;Vuijk et al, 2010;Salvador-Carulla et al, 2013;Pulina et al, 2019). Furthermore, limitations in social skills, emotional competencies and behavioral problems affect social participation of these children (Kavale and Forness, 1996;Baglio et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite its sizeable prevalence, borderline intellectual functioning is a rarely studied topic not only in children but also in adults, and information on it is fragmentary. [ 23 24 ] Melby et al . [ 25 ] (Tingvoll, Norway) have assessed young adults (19-year-olds) with borderline intellectual functioning, using the Schedule for Affective Disorder and Schizophrenia for School-age Children Present and Lifetime (K-SADS P/L) instrument, and reported that they had excess risk of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…The cognitive profile of children with BIF differs from that of typically developing children, with the lowest scores on the index related to working memory on the Wechsler Intelligence Scale for Children, Fourth Edition test [ 9 ]. In children and adolescents with BIF, total cognition, verbal and visual performance, processing speed, and working memory decline over time [ 10 ].…”
Section: Clinical Characteristicsmentioning
confidence: 99%